Is my drinking a problem? A community-based alcohol intervention programme post-Haiyan in Tacloban City (Western Pacific Surveillance and Response, 2015)
Problem: Evidence on alcohol use following disasters is scarce. After Typhoon Haiyan in the Philippines we wanted to determine whether there were alcohol-related problems among the disaster survivors and to strengthen the appropriate local health service support in Tacloban City.Context: Tacloban City is a highly urbanized city that was one of the areas worst hit by Typhoon Haiyan. Prior to Haiyan there was very little support for people with alcohol problems, and the rehabilitation facility was located about 40 km away.Action: A pilot community-based alcohol intervention programme was conducted that included: assessment of the extent of alcohol problems in the community and health-care workers baseline knowledge and skills; training of health-care workers on primary care alcohol intervention provision; and community outreach with post-training supervision.Outcome: The alcohol screening found 26 (22%) of those attending health care facilities would benefit from some form of alcohol intervention. Health-care workers knowledge on basic alcohol intervention was low. This was strengthened during the training, and at outreach clinics the trained health-care workers were able to identify people with alcohol problems and provide them with treatment plans.Lessons learnt: We learnt that there was a problem with alcohol in Tacloban City and that it was possible to run an alcohol intervention programme in the community using minimal resources. Addressing alcohol-related issues in the community is an important public health intervention. While there is a need for policies and guidelines at the national level, a community-based intervention is possible to establish with referral mechanism to specialized care. Training modules for such programs can be further developed and institutionalized.